"Doing research is not beyond my reach": The reconstruction of College English teachers' professional identities through a domestic visiting program. (April 2022) - Bao, Jie; Feng, Dezheng (William)
Abstract: This study explores the trajectories of Chinese College English teachers' identity reconstruction throughout a domestic visiting study program. Three teachers in a one-year program were followed and data were collected through interview and observation. Analysis shows that a research dimension was either activated or reinforced in their professional identities. Three distinctive trajectories of development were identified: from 'unreconciled dreamer' to 'fulfilled research practitioner', from 'passive adapter' to 'agentic researcher-teacher', and from 'invisible layperson' to 'confident teacher-researcher'. The reconstruction of their professional identities is explained in relation to the interplay between personal factors and the mediating context reified by the program. Highlights: College English teachers reconstruct their identities through in-service programs. Interview and observation revealed three trajectories of identity development. Dream actualization, mindset change and self-perception improvement are identified. Influencing factors from personal and contextual levels are discussed.